2020
DOI: 10.1182/blood.2019002385
|View full text |Cite
|
Sign up to set email alerts
|

Coding and noncoding drivers of mantle cell lymphoma identified through exome and genome sequencing

Abstract: Mantle cell lymphoma (MCL) is an uncommon B-cell non-Hodgkin lymphoma (NHL) that is incurable with standard therapies. The genetic drivers of this cancer have not been firmly established and the features that contribute to differences in clinical course remain limited. To extend our understanding of the biological pathways involved in this malignancy, we performed a large-scale genomic analysis of MCL using data from 51 exomes and 34 genomes alongside previously published exome cohorts. To confirm our findings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 77 publications
2
48
2
2
Order By: Relevance
“…Additionally, there is considerable variability in which genes are affected in each individual patient (Table S5). These circumstances made it less feasible to identify driver genes in our MCL cohort, although drivers appeared mutated at a similar rate as reported previously [5,6,18]. However, when resorting to the CGI, we identified 64/75 patients (84%) that had mutations in either one established driver gene variant in cancer or a predicted driver mutation by OncodriveMUT (Table S6), which correspond to 138/382 identified variants.…”
Section: Landscape Of Mutations In MCL Accurately Detected From Ffpe Samplessupporting
confidence: 66%
See 2 more Smart Citations
“…Additionally, there is considerable variability in which genes are affected in each individual patient (Table S5). These circumstances made it less feasible to identify driver genes in our MCL cohort, although drivers appeared mutated at a similar rate as reported previously [5,6,18]. However, when resorting to the CGI, we identified 64/75 patients (84%) that had mutations in either one established driver gene variant in cancer or a predicted driver mutation by OncodriveMUT (Table S6), which correspond to 138/382 identified variants.…”
Section: Landscape Of Mutations In MCL Accurately Detected From Ffpe Samplessupporting
confidence: 66%
“…The frequency of patients with mutated CCND1 was lower than previously reported. Studies that reported higher number of CCND1 mutations analyzed a large proportion of peripherial blood samples and had a much higher number of cases classified as high-risk MIPI than our study (60-91% vs. 45%, respectively) [6,18]. We also found that NSD2 was mutated at a lower frequently than expected [13].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Mutations in TP53, SMARCA4, CELSR3, CCND1 and KMT2D have been found to negatively affect the response to venetoclax-based therapies. [109][110][111] The median survival is 3-5 years, and the majority of cases remain incurable, with multiple relapses. Besides standard chemotherapy, treatment options currently comprise many new drugs such as ibrutinib, lenalidomide, bortezomib, temsirolimus, and venetoclax.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…The genomic landscape of MCL is heterogeneous, and comprises mutations in genes involved in DNA damage response ( ATM and TP53 ) and Notch signalling ( NOTCH1 and NOTCH2 ), and in genes affecting RNA metabolism and splicing ( EWSR1 , DAZAP1 , and HNRNPH1 ). Mutations in TP53 , SMARCA4 , CELSR3 , CCND1 and KMT2D have been found to negatively affect the response to venetoclax‐based therapies 109–111 …”
Section: Small B‐cell Lymphomasmentioning
confidence: 99%